A novel method for chloride-induced corrosion analysis incorporating consistent ionic diffusivity and concrete resistivity. (15th February 2023) - Dong, Bin; Yu, Yuguo; Gao, Wei; Zhao, Gaofeng
Highlights: A novel electrochemical modelling technique is proposed. The detailed finite-element-based solution algorithm is presented. The multi-ionic transportation is coupled with corrosion propagation. The explicit evaluation of concrete resistivity is avoided. Precise prediction of corrosion propagation is achieved. Abstract: Corrosion is one of the most serious durability concerns for steel reinforced structures exposed to coastal and offshore environments. In engineering practice, the corrosion process of steel reinforcements is closely influenced by the electrical resistivity of cover material. Misinterpretations of this property would substantially result in unreliable corrosion assessment. In this paper, an electrochemical model coupling ionic transportation with steel corrosion for the chloride-induced corrosion analysis is newly established. Through the proposed method, the explicit evaluation of the material resistivity is avoided. Instead, the resistivity is reflected by the ionic diffusivity under the effect of consistent ionic transportation and electric current during the corrosion process. To solve the highly nonlinear numerical system, a finite element-based solution algorithm is also presented in detail. The proposed model is first compared with the reported method in both uniform and nonuniform corrosion scenarios. While both methods yield identical results in a uniform case, the major advantage of the present model is reflected in the modelling of nonuniform corrosion. By further validating against reported experiments, the proposed method is of demonstrated capability and practical values to assess chloride-induced corrosion under time-variant service conditions and complex reinforcement configurations.